변화된 교육환경에 따른 환경공학교육의 방향설정 연구 - 전항배(Hang Bae Jun); 전동걸(Dong Jie Tian); 임현우(Hyun Woo Lim); 양효진(Hyo Jin Yang) (Daehan hwan'gyeong gonghag hoeji, 2012)
Recently, regional society requires engineers to understand the international affairs and to be global experts endowed with leadership. General education appropriate to engineers should fulfill these needs and provide wide understandings in humanity. General sciences education should be also reinforced for the students taking low level science courses under 7th education program to improve learning ability of the major subjects in college. A general education component including humanity for the engineers could be trained continuously from primary school to college under the 2009 revised education program. Various opportunity for education should be provided through the special curriculum development at the college or department level, which trains experts who fulfill the need of community. Multi-major program is a substitute for offering the educational opportunity to the students in environmental engineering, one of multidisciplinary programs. Emphasized criteria of the curriculum requirements and adequate contents of general education need be also developed for supporting the students to take advanced courses in major. 최근의 사회는 엔지니어에게 국제사회와 미래를 이해할 수 있고, 리더십을 갖춘 전문기술자가 될 것을 요구하고 있다. 전문교양교육은 이러한 요구를 만족시켜 주어야 하며, 글로벌형 인재를 양성할 수 있도록 강화돼야 한다. 7차 교육과정 이후 소홀해진 과학교육으로 인해 저하된 이공계기초 교양교육을 강화시켜 공과대학 학생들의 전공수학능력을 향상시켜야 한다. 엔지니어의 인성 및 기초교양 교육은 2009 교육과정을 통하여 초 중 고부터 대학으로 이어지는 연속적이고 체계적인 교육과정으로 완성될 수 있다. 아울러 대학 및 학과특성화 과정을 통하여 다양한 교육의 기회를 제공해주고, 사회가 요구하는 필요한 인재를 양성하도록 해야 한다. 환경공학은 학제간 융복합적 성격이 강하기 때문에 다전공제도를 적극 활용하는 것이 바람직하고, 이공계기초 과목의 이수기준을 강화시킬 필요가 있으며, 환경공학 맞춤형 교양교육컨텐츠를 개발할 필요가 있다.